Estudo da deformação permanente de concretos asfálticos aplicados em campo - Pires, Diego Menegusso (2020)
Transport on highways, mainly on asphalt pavement, is crucial for many countries around the globe, being relevant to the economic and social contexts of a country. Another key factor is the mechanical behaviour of asphalt mixtures, result of the materials used, traffic and weather corrosion, amongst other conditions, and is directly linked to its on-field performance, being expressed, by the mechanical properties acquired, through scientific in lab studies. It is of the highest priority the knowledge of the behaviour of the mixtures used for the sizing and specification of the pavement layers, for them to be used properly on State-run roads. It is considered that permanent deformation phenomenon is a key effect found in asphaltic pavements. In this way, this research aims to evaluate asphaltic mixtures utilized on the field, with different aggregates and asphalt binders, as well as several grain size ranges recommended by the road agencies that oversee the state highways (DAER and DNIT), seeking to understand how its characteristics act on resisting the permanent deformation phenomenon. Furthermore, it presents relationships between the scales: binder; mixture and; track. To carry out the study, eight mixtures were collected and evaluated the mechanical behaviour of these mixtures through lab and field examination, focusing on permanent deformation, as defined on the study Flow Number, Hamburg Test and the binders by the Multiple Stress Creep Recover study. In addition, the stretches of road were monitored to evaluate permanent deformation of the layers. With the analysis of the results, it was possible to verify the modified binders by polymer and rubber demonstrated a satisfactory performance on permanent deformation when compared to conventional binders. The stiffness of asphaltic mixtures under high temperatures is a predictor of huge importance by the permanent deformation performance, on a relation of strength gain with respect to rutting, as of gain of stiffness. It was verified that the stiffness behaviour of asphaltic mixtures under high temperatures is directly related to the stiffness of the asphaltic binders, on field, suggesting the performance against permanent deformation is strongly connected to the behaviour of the binder-scale.